Autonomous Vehicles Require Socio-Political Acceptance—An Empirical and Philosophical Perspective on the Problem of Moral Decision Making - Bergmann, Lasse T.; Schlicht, Larissa; Meixner, Carmen; König, Peter; Pipa, Gordon; Boshammer, Susanne; Stephan, Achim (Frontiers in Behavioral Neuroscience, 2018)
Autonomous vehicles, though having enormous potential, face a number of challenges. As a computer system interacting with society on a large scale and human beings in particular, they will encounter situations, which require moral assessment. What will count as right behavior in such situations depends on which factors are considered to be both morally justified and socially acceptable. In an empirical study we investigated what factors people recognize as relevant in driving situations. The study put subjects in several “dilemma” situations, which were designed to isolate different and potentially relevant factors. Subjects showed a surprisingly high willingness to sacrifice themselves to save other, took the age of potential victims in a crash into consideration and were willing to swerve onto a sidewalk if this saved more lives. The empirical insights are intended to provide a starting point for a discussion, ultimately yielding societal agreement whereby the empirical insights should be balanced with philosophical considerations.